Integrating Intelligent Consumer Behavior into Procedure Analysis for Campus Business Information System Development - Sugiarto, Sugiarto; Atmaja, Pratama Wirya; Novembrianto, Rizka; Kurniati, Ely; Widnyani, Ni Made (ILKOMNIKA, 2026)
This study develops SIPUS, a campus business information system for the Business Management Unit (BPU), by integrating procedure analysis with intelligent consumer behavior considerations to improve both operational correctness and user-facing service experience. The research applies a requirements-driven approach in which current procedures are documented, key procedural issues are identified (e.g., fragmented coordination, unclear responsibility boundaries, inconsistent schedule handling, non-explicit handoffs, and incomplete decision gates), and the findings are translated into traceable functional requirements and user-oriented acceptance criteria. SIPUS implementation is organized across five BPU service domains, including facility rentals and food stall participation, and emphasizes standardized workflow control points such as availability validation, conflict detection, closure status handling, approval routing where applicable, and payment verification. System validation combines stakeholder review of procedure–requirement–implementation alignment with user-oriented evaluation using CSUQ. CSUQ results show consistently high ratings on a 1–7 scale, with an overall mean of 5.79 (82.7% of the maximum score) and low dispersion (SD = 0.12), indicating favorable perceived usability and interaction quality. Overall, the results demonstrate that incorporating consumer-oriented evidence during requirements formulation strengthens alignment between operational procedures, implemented system behavior, and user expectations in campus service delivery.